SOME ASPECTS OF INFLUENCE OF PHOTOPERIOD ON MUGA SILKWORM, ANTHERAEA ASSAMA WESTWOOD (LEPIDOPTERA : SATURNIIDAE) - MAHANTA, H. C.; GOSWAMI, M. C. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1986)
The role of photoperiod on the developmental processes as well as in the induction of pdiapause in A. assama is presented. Photoperiods of short day lengths (of high intensities ugh slow down developmental rates, are not effective in the induction of pupal diapause, w short-day photoperiods of very low intensities are only effective in inducing diapause in this inst The effect of photoperiod on egg-laying and hatching is also discussed in this study.